Outcomes of Human Immunodeficiency Virus infected children admitted to a paediatric intensive care unit in Cape Town, South Africa - Salie, Mogamat Shamiel (Department of Paediatrics and Child Health, 2016)
During the mid to late 1990's, nearly all HIV infected children admitted to South African paediatric intensive care units died. This was in the context of an increasing HIV epidemic in Sub-Saharan Africa, a limited number of intensive care beds in public hospitals and the South African government refusing to supply antiretroviral medication to public sector patients. HIV infected children all die without ARV medication, and it resulted in an increase in the South African under-5 mortality rate. In this context critically ill HIV infected children were often denied PICU admission. Developed countries introduced ARV medication in the early 1990's and the South African government only started supplying ARV medication in late 2003. When ARV medication became available in South Africa, it was started on the basis of the individual child's clinical and immunological status and there was not much published data on initiation of ARV therapy in critical ill children in intensive care units. Many HIV infected children had recurrent hospital admissions and many children died before initiating ARV medication. HIV infected children are not only susceptible to the normal bacteria and viruses, but at increased risk of opportunistic and mycobacterial infections. CMV has increasingly been recognized as a common co-infection with PCP, but has been difficult to diagnose and treat effectively. We retrospectively reviewed all HIV exposed and infected children admitted to our PICU in 2009. In addition to our standard treatment, we initiated ARV medication as soon as logistically possible and children with suspected CMV infections were empirically treated with gancyclovir.